Effect of ultraviolet exposure and palm fibre/fibreglass direction on composite - Tri Partuti; Muhammad Iqbal Bariq; Yanyan Dwiyanti; Adhitya Trenggono; Erlina Yustanti (Jurnal Teknika, 2022)
Composite can be used as an alternatif material to replace items made of wood. Wood usually not resist to water and prone to weathering in outdoor application. Composite is expected to overcome the weakness of wood. This research aims to make composite with different direction of palm fibre/fibreglass as filler and unsaturated polyester resin as matrix with hand lay-up method, also to find out whether its suitable for outdoor application or not. Ultraviolet (UV) exposure is one of element at outdoor environment that can damage polymer matrix composite. UV exposure for 1, 2 and 3 months was carried out on composites with different palm fibre directions: unidirectional, bidirectional and random. To find significant relationship between fibre direction and tensile strength, and also UV exposure time and tensile strength, correlation test was carried out using SPSS. The result shows that before UV exposure, tensile strength of composite with random, unidirectional and bidirectional palm fibre were 29.97 MPa, 28.53 MPa, and 20.92 MPa, respectively. After 3 months UV exposure, mass of composite with random, unidirectional, and bidirectional palm fibre decreased by 1.14%, 1.34%, and 1.39%, respectively. The correlation test showed that there was no significant correlation between palm fibre directions and tensile strength, and also time of UV exposure and tensile strength with correlation coefficients (r) = -0.504 and -0.237, respectively. Composite colour changed become more faded after 3 months UV exposure. Intensity change of FTIR spectra showed the degradation of composite at wave number about 1750-1725 cm-1, 1230–1260 cm−1 and 700 cm−1. Based on its tensile strength, composite can replace wood with PKKI NI-5 2002 standard for quality code E14 (for unidirectional and bidirectional palm fibre) and E12 (for random palm fibre). Aesthetically, the fading of the composite colour after 3 months UV exposure indicates that composite is not suitable for outdoor application yet.